Training of local stakeholders on animal nutrition in Son La Province, Vietnam - Tran, Thi Bich Ngoc; Tran, Viet Phuong; Nguyen, Thien Truong Giang; Do, Trong Hieu; Nguyen, Tien Sinh; Dao, Thi Thu Hang; Atieno, Mary; Peters, Michael; Duncan, Alan J. (International Livestock Research Institute, 2024)
Livestock production in the Northwest Highlands (NWH) of Vietnam, particularly in Son La Province, faces significant challenges. Limited knowledge and skills among farmers in livestock production practices, particularly in feed and feeding strategies, are major constraints that impede livestock productivity1. In the Livestock CRP project (Li-chan), farmers in four villages of Chieng Chung and Chieng Luong communes, Mai Son district, were trained on feeds and feeding regimes, however, the farmer’s receptivity to knowledge was still limited due to the short project duration and other operational barriers. Acute winter (dry season) feed shortage, lack of high-quality forage varieties and limited capacity in animal nutrition techniques are pressing issues for livestock producers in the region. The reliance on traditional forage varieties, such as Napier grass, further constrains productivity, and this presents an opportunity for introducing and promoting improved forage varieties in the region.